2020
DOI: 10.1038/s41598-020-67291-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased Alcohol Consumption in Mice Lacking Sodium Bicarbonate Transporter NBCn1

Abstract: christian Aalkjaer 5 , ebbe Boedtkjer 5 & inyeong choi 2 ✉ The previous reports on an addiction vulnerability marker in the human SLC4A7 gene encoding the na/Hco 3 transporter NBCn1 suggest that this pH-regulating protein may affect alcohol-related behavior and response. Here, we examined alcohol consumption and sensitivity to the sedative effects of alcohol in male NBCn1 knockout mice. These mice displayed lower pH in neurons than wildtype controls, determined by intracellular pH in hippocampal neuronal cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Knockouts of these neuronal NCBTs protect mice from seizures incidence and mortality in response to pentylenetetrazol, pilocarpine, or NMDA [14,20,22]. Among neuronal NCBTs, NBCn1 and NDCBE affect glutamate neurotransmission [20][21][22]149] and thus are of particular interest with respect to their potential involvement in schizophrenia. NBCn1 interacts with the NMDA receptor subunit GluN1 and constitutes a protein complex in the postsynaptic density [20,151].…”
Section: Ncbtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockouts of these neuronal NCBTs protect mice from seizures incidence and mortality in response to pentylenetetrazol, pilocarpine, or NMDA [14,20,22]. Among neuronal NCBTs, NBCn1 and NDCBE affect glutamate neurotransmission [20][21][22]149] and thus are of particular interest with respect to their potential involvement in schizophrenia. NBCn1 interacts with the NMDA receptor subunit GluN1 and constitutes a protein complex in the postsynaptic density [20,151].…”
Section: Ncbtsmentioning
confidence: 99%
“…This inhibition protects neurons from NMDA-mediated excitotoxicity [13]. Furthermore, mice with genetic deletion of some NCBTs such as NBCn1, NCBE, and NDCBE develop less excitable membranes, higher resting potential, or decreased glutamate release [20][21][22], and they are less susceptible to repetitive discharges in response to pentylenetetrazol, pilocarpine or NMDA [20,22]. Taken together, it is conceivable that the lowered brain pH in schizophrenia patients will influence synaptic activities involved in the pathophysiology of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Although NBCn1 has a broad expression profile in normal tissue [ 28 ], most non-cancerous cells experience a near-normal pH o and a moderate metabolic acid load that they can adequately eliminate even if NBCn1 is inhibited. Accordingly, global constitutive NBCn1 knockout mice show only modest phenotypes until they are challenged, for instance, by aging, augmented acid-loading, substance abuse, carcinogen treatment, or infusion with vasoactive agonists [ 28 33 ]. The multiple splice variants of SLC4A7 , with distinct tissue-specific expression profiles [ 34 , 35 ], may permit predominant targeting of NBCn1 in disease-affected tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that alcohol consumption is high in mice with targeted inactivation of a pH-regulating protein found in many cells, including neurons [21]. These mice have low pH in neurons and display increased responses to alcohol due to the development of increased motivation to drink alcohol.…”
Section: Introductionmentioning
confidence: 99%